Politicized mediatization of a sports incident in conditions of information confrontation - Baykova I.A.; Bykova E.V.; Gavra D.P.; Oleynikov S.V. (Theory and Practice of Physical Culture, 2024)
Objective of the study was to identify the speech means of defense rhetoric in Russian state media in line with the mediatization of a sports incident using the example of the Kamila Valieva doping scandal during the 2022 Beijing Olympics. Methods and structure of the study. The empirical base included media texts of Russian federal media from 10.02.2022 to 20.02.2022, collected by the Semanticforce.net system using the keyword “Kamila Valieva” in the text, title or subtitle. In the selected texts, metaphors of war are highlighted, since “metaphoricality is one of the most important features of modern propaganda and political speech”. Results and conclusions. The authors found that during the information confrontation, Russian state media used communication strategies largely based on military rhetoric. The media strategy of the domestic mass media was to formulate in the audience an idea of the war declared by the Western world against Russian sports and the country as a whole. The authors conclude that in the context of global political confrontation, any incident involving athletes of the opposing sides is highly likely to be mediatized using a communication algorithm similar to that discussed in this article.